Computer-assisted needle trajectory planning and mathematical modeling for liver tumor thermal ablation: A review - Rui Zhang; Shuicai Wu; Weiwei Wu; Hongjian Gao; Zhuhuang Zhou (Mathematical Biosciences and Engineering, 2019)
Radiofrequency ablation (RFA) and microwave ablation (MWA) have become an important means for treating liver tumors. RFA and MWA are a minimally invasive therapy which involves an ablation applicator or needle (i.e., radiofrequency electrode or microwave antenna) inserted percutaneously into a tumor under the guidance of medical imaging, so as to destroy the tumor in situ by heating-induced coagulation necrosis. Treatment planning, particularly needle trajectory planning, is crucial to RFA and MWA. In clinical procedures, however, needle trajectory planning still relies on the personal experience of clinicians. Manual needle trajectory planning is tedious and may cause inter-operator difference. Therefore, computer-assisted needle trajectory planning techniques are of clinical value and have been extensively explored. However, a literature review that focuses on computer-assisted needle trajectory planning for liver tumor RFA and MWA has not been reported. In this paper, we conducted an extensive review on computer-assisted needle trajectory planning for RFA and MWA of liver tumors. Fundamentals of needle trajectory planning are summarized. Algorithms for single-needle and multi-needle trajectory planning are analyzed. Shortcomings of current computer-assisted needle trajectory planning algorithms are discussed and future developments are suggested.